The Czech GovernmentÂ´s Strategy for Reducing Inequality - Pichanic, Mikulas; Stankova, Anna (European Scientific Journal, ESJ, 2018)
Inequality as measured by the distribution of income between rich and poor countries has narrowed globally. However, the story is less pleasing within individual countries. This paper analyses the situation in one postcommunist transitional country. The aim of the paper is to answer whether the generally-accepted opinion about Czech society being egalitarian is true. We started with an analysis of wealth inequality within EU countries. The first conclusion based upon EUROSTAT and World Bank data shows the inequality between developed EU members and post-communist countries and the authors analyze some of the contributing factors. Next, we analyze inequality through the prism of three different methods to discover whether the commonly-proclaimed opinion about the egalitarian nature of Czech society is true or whether the reality is different. The first factor is differentiation among workers. The analyses clearly support the conclusion that inequality of workers in Central European post-communist countries will hardly reach the income level corresponding to their counterparts of groups in the A and B categories of workers in the developed economies of the EU. The second is the growth of crony capitalism (as measured by the crony capitalism index). A value of 12.53 indicates a high level of interaction between the government and rent seekers and requires the immediate implementation of appropriate measures. The third is social and economic status. Social status has been predominantly influenced by access to education, family structures, social capital (interaction with groups), and pre-existing income inequality. Access to inexpensive education represents the most important factor in reducing inequality, regardless of comparatively low government spending (within the EU). The paperâ€™s conclusions see the greatest inequality in pre-existing wealth (created by restitutions after the fall of the communist regime) and thereafter the possibility to participate on a free market of investments. Inequality has been growing despite the generally-accepted supposition that Czech society is egalitarian.